Complex treatment of Pellucid Marginal Degeneration (a case report) - B. E. Malyugin; S. B. Izmaylova; E. P. Poruchikova; A. Y. Semykin (Офтальмохирургия, 2015)
Purpose. To assess the results in a step-by-step complex treatmentof a patient with pellucid marginal degeneration (PMD) of cornea and cataract.Material and methods. Patient N., male, 52 years old, who complained on a low and deteriorating vision was diagnosed with pellucid marginal degeneration, cataract and lens subluxation in both eyes. Patient’s examinations included visometry, keratometry, anterior optical coherence tomography, corneal topography, and confocal microscopy. Then the step-by-step procedures in the left eye of the patient were performed including intrastromal keratoplasty with implantation of PMMA corneal ring segment, followed by UV cross-linking (after 3 months) and then phacoemulsification with toric IOL implantation 6 months later.Results. Both the uncorrected visual acuity (UCVA) and the best corrected visual acuity (BCVA) increased, accompanied by flattening of the central cornea, increasing flat and lowering steep corneal meridians. The BCVA became 0.6, and astigmatism decreased from 11.0D to 4.0D 3 month after intrastromal keratoplasty. The BCVA (sph -4.0 cyl -3.5 ax 115º) after UV cross-linking was unchanged while the final UCVA after toric IOL implantation was 0.8.Conclusion. The step-by-step approach including consecutively intrastromal keratoplasty with implantation of PMMA corneal ring segments, UV cross-linking, provided a stabilization of ectasia and an astigmatism decrease, phacoemulsification with toric IOL implantation allowed to increase considerably visual functions and to achieve the complete visual r ehabilitation.